From repairing the damaged landscape to restoration project - Céline Granjou; Stéphanie Gaucherand; Elaine Chanteloup (Revue de Géographie Alpine)
The study adopts an empirical sociological approach to analyse how the objectives behind the revegetation of ski trails and runs in the French alpine resort of Alpe d’Huez have evolved since the 1970s. A revegetation programme was first introduced to repair the scars left by the works conducted to equip the resort with infrastructures, and then, over time, it became a more complex restoration project. At first, revegetation techniques were developed to fight soil erosion, but soon also became associated with the idea of “turning the mountain green again”. Now, 40 years later, revegetation is aimed at restoring both a natural ecosystem and a cultural landscape. The ski resort’s managers, local farmers, technicians, and those conducting research in the area share a common desire to promote autochthony, which in some cases runs the risk of reproducing folklore. Far from adopting an overriding ethical perspective, the study suggests that the area’s physical characteristics, specific history and configuration of local actors have shaped and continue to shape both the manner in which ecological restoration is implemented, through political choices and technical decisions, and the debates it gives rise to. The study concludes by examining the specificity of the findings for Alpe d’Huez and discussing their validity for other alpine ski resorts.